Characteristics and molecular mechanism of drug-tolerant cells in cancer: a review - Liang, Xian-Wen; Liu, Bing-; Chen, Jia-Cheng; Cao, Zhi; Chu, Feng-ran; Lin, Xiong; Wang, Sheng-Zhong; Wu, Jin-Cai (Frontiers in Oncology, 2023)
Drug resistance in tumours has seriously hindered the therapeutic effect. Tumour drug resistance is divided into primary resistance and acquired resistance, and the recent study has found that a significant proportion of cancer cells can acquire stable drug resistance from scratch. This group of cells first enters the drug tolerance state (DT state) under drug pressure, and gradually acquires stable drug resistance through adaptive mutations in this state. Although the specific mechanisms underlying the formation of drug tolerant cells (DTCs) remain unclear, various proteins and signalling pathways have been identified as being involved in the formation of DTCs. In the current review, we summarize the characteristics, molecular mechanisms and therapeutic strategies of DTCs in detail.